A Narrative Review of Ultrasonographic Features of Umbilical Lesions in Children and Our Experience - Seyed Ali Alamdaran; Alireza Nakhaei; Ehsan Hassan Nejad; Amir Behforouz (Mashhad University of Medical Sciences, 2023)
Background: The umbilicus is the fibrous remnant of the fetal attachment of the umbilical cord. Ultrasonography is the preferred imaging modality for the evaluation of umbilical lesions. We present our experience and a review of ultrasound findings of umbilical lesions in children that may differentiate these lesions.Methods: A query was conducted on online databases to identify and review articles in English studying umbilical lesions and their ultrasound features in children until September 2022. In some cases, the authors' unpublished experiences were also used due to insufficient ultrasound information in the literature.Results: The thickness of the normal urachus is 2.5- 4 mm in newborns, and after the infancy period, it reduces to less than 2 mm. An increase in its thickness, generally or focally, indicates a patent urachus or urachal sinus. The normal cord or its remnant is observed as a hypoechoic mass surrounded by an elevated skin ring during infancy. The abdominal extension of the cord remnant suggests a patent urachal or omphalomesenteric remnant. On ultrasound, umbilical polyps are deep-seated lesions with mixed or hyper-echoic echo texture that can help differentiate them from umbilical cord remnants or umbilical granulomas. Ultrasonographic findings of omphalitis or the infected cord remnant are enlarged umbilicus as a large mass-like lesion associated with edema of peri-umbilical skin and subcutaneous tissues.Conclusion: As evidenced by the results of this study, ultrasound can be used as a valuable complementary assessment tool for clinicians, allowing for assessing umbilical lesions and choosing the correct approach to treating these lesions. Keywords: Omphalomesenteric duct, Ultrasound, Umbilical lesion, Umbilicus, UrachusBackground: The umbilicus is the fibrous remnant of the fetal attachment of the umbilical cord. Ultrasonography is the preferred imaging modality for the evaluation of umbilical lesions. We present our experience and a review of ultrasound findings of umbilical lesions in children that may differentiate these lesions.Methods: A query was conducted on online databases to identify and review articles in English studying umbilical lesions and their ultrasound features in children until September 2022. In some cases, the authors' unpublished experiences were also used due to insufficient ultrasound information in the literature.Results: The thickness of the normal urachus is 2.5- 4 mm in newborns, and after the infancy period, it reduces to less than 2 mm. An increase in its thickness, generally or focally, indicates a patent urachus or urachal sinus. The normal cord or its remnant is observed as a hypoechoic mass surrounded by an elevated skin ring during infancy. The abdominal extension of the cord remnant suggests a patent urachal or omphalomesenteric remnant. On ultrasound, umbilical polyps are deep-seated lesions with mixed or hyper-echoic echo texture that can help differentiate them from umbilical cord remnants or umbilical granulomas. Ultrasonographic findings of omphalitis or the infected cord remnant are enlarged umbilicus as a large mass-like lesion associated with edema of peri-umbilical skin and subcutaneous tissues.Conclusion: As evidenced by the results of this study, ultrasound can be used as a valuable complementary assessment tool for clinicians, allowing for assessing umbilical lesions and choosing the correct approach to treating these lesions.